A model for predicting sand production in horizontal wells (2012)
Sand produced along with oil and gas causes operational, safety, environmental and severe economic challenges. The cost of installing sand control facilities which may not really be needed could also be substantial. Therefore, determining the critical flow rate for the onset of sand production is very important. There are several published studies on sanding in vertical wells, but few on horizontal wells, which have now become very prominent in the industry. The aim of this study was to develop a simple but robust model for predicting sand rates in horizontal wells. A novel geomechanical model incorporating gravity, buoyancy, drag and lift forces was developed and validated with data from 3 oil fields in the Niger Delta. The results showed that sand production could take place in horizontal wells even at low production rates but increases at high production rates in the fields of study. Critical sand rate is also affected by horizontal well length, fluid viscosity and diameter of the sand particles.